(3MbGFb GdJaSjQs - (3eMeO Hf GdMSjf Hf eMeO Hf ehSi GdCROj GdSdej GdfjSGHhQj, CHh YHO GdQMef,J (B412 (3g` s ((3CMeO CeHQ OGhO Hf EHQGgje Hf eMeO s)
(3ChdgG (B:s
(3GdMeO ddI GdPi NU Cgd GdMbGFb HNhGU SQGjQ hLYdge Ggd dagegG s
(3BNQgG (B:s
(3HGdLhOI hGdSNGA BNQ cJGH MbGFb GdJaSjQ s
(3GdfSNI HgG MhGTs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B258s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH (B(23010) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs